Analysis of a hybrid (topping/bottoming) ORC based CHP configuration integrating a new evaporator design concept for residential applications. (September 2019) - Pereira, João S.; Ribeiro, José B.; Mendes, Ricardo; André, Jorge C.
Highlights: Design principles of an evaporator for a residential scale ORC based CHP system. Residential ORC based CHP request direct vaporization to retrofit combi-boilers. Integration of a post-heater and ORC-evaporator creating a hybrid CHP scheme. CHP thermal energy is produced stepwise in a hybrid (topping/bottoming) scheme. Primary energy savings and net power output are increased in hybrid configuration. Abstract: The recommended design principles for the development of evaporators for ORC based micro-CHP systems attempting to retrofit the current combi-boilers are presented and discussed in this paper. From those principles, among which is the need of organic fluid direct vaporization, emerged a hybrid (topping/bottoming) CHP configuration in which the thermal energy is produced stepwise: firstly in the ORC-condenser and then in a post-heater, that is integrated on the ORC-evaporator, directly with the combustion gases. A model of this configuration was developed to determine the fraction of the CHP water heating process performed in the post-heater that maximizes the primary energy savings and ORC net power output for a wide range of CHP operating conditions. When compared to a standard CHP configuration, this solution show benefits for the greater part of those conditions. Besides solving the safety issue posed by the ORC-evaporator requirements and the performance benefits shown, this configuration has an additional positive side effect: the decrease of the combustion gases' temperature before they reach the organic working fluid heat-exchanger section in the ORC-evaporator that leads to a reduction of the risk of the working fluid thermal degradation.